Development of Android-Based Student Performance Tool (Tunersindro) to Improve Work Readiness of Vocational High School Students - Bambang Sudarsono; Fatwa Tentama; Fanani Arief Ghozali; Suhono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Work readiness has an effect on the unemployment rate for Vocational High School (SMK) graduates. Work readiness can be improved by improving learning patterns and tools. This study aims to develop learning aids, test the feasibility and effectiveness of the product. The research design used is the ADDIE Research Development (R&D) design with the stages of Analysis, Design, Development or Production, Implementation or Delivery and Evaluations. The research site is at SMK Muhammadiyah 2 Tempel with research subjects of 134 students, 14 teachers of Automotive Engineering Vocational School and 5 automotive industry practitioners. Data collection techniques used were questionnaires and tests with interview research instruments, media and product questionnaires and practice test sheets. Android-based student performance aids (Tunersindro) have a very high feasibility of being used in vocational learning. Not only that, with two trials, Tunersindro has a very high level of effectiveness in increasing the work readiness of SMK students Keywords: Improving Work Readiness, Students Performance Aid, Development Tool Tunersindro